Nitrogen Dynamic from Applied Rice Straw Compost in Flooded Soil - Linca Anggria; T. Rustaman; A. Kasno (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2014)
Abstract. Nitrogen is the main fertilizer to increase rice production. Nitrogen fertilizer use efficiency is affected by organic matter content in the soil. Understanding decomposition and nitrogen release of plant materials is important to better manage organic inputs. The objective of this research was to study the nitrogen dynamics on flooded soil with rice straw compost application. The experiment was carried out in green house of Indonesian Soil Research Institute (ISRI) on October 2010 to January 2011. Soil samples were taken from Ciruas, Banten. The analysis of ammonium and nitrate were conducted 14, 20, 30, 40, 50, and 60 days after planting. The result showed that ammonium and nitrate in soil with straw compost applications were lower than that of chemical fertilizer application. After day 20, the concentration of ammonium in soil decreased to the same level for all treatments. The concentration of nitrate, after increase on day 40 decreased until the last obeservation (day 60). Nitrogen concentration in straw was higher under chemical fertilizer than that of straw compost application. In rice grain, N concentrations were not significantly different among the two treatments. Abstrak. Nitrogen adalah pupuk utama untuk meningkatkan produksi beras. Efisiensi penggunaan pupuk nitrogen dipengaruhi oleh kandungan bahan organik dalam tanah. Pemahaman mengenai dekomposisi material tanaman adalah sesuatu yang penting untuk lebih baik dalam mengelola penambahan bahan organik. Tujuan dari penelitian ini adalah mempelajari dinamika hara nitrogen pada tanah sawah dengan penambahan bahan organik (kompos jerami). Penelitian dilakukan di rumah kaca, Balai Penelitian Tanah pada bulan oktober 2010 sampai Januari 2011. Sampel tanah berasal dari Ciruas, Banten. Analisis amonium dan nitrat dilakukan pada hari ke-14, 20, 30, 40, 50, dan 60 setelah tanam. Hasil penelitian menunjukkan bahwa amonium dan nitrat dalam tanah dengan penambahan kompos jerami lebih rendah dibandingkan dengan pupuk kimia. Umumnya setelah hari ke-20, konsentrasi amonium di dalam tanah menurun untuk semua tingkat perlakuan. Sedangkan konsentrasi nitrat, setelah meningkat pada hari ke-40 konsentrasi menurun hingga hari terakhir (hari ke-60). Konsentrasi nitrogen pada jerami menunjukkan bahwa aplikasi pupuk kimia lebih tinggi dibanding kompos jerami. Sedangkan konsentrasi N pada gabah padi tidak berbeda nyata.